Re-appointment of UMP’S VC - UMP, PNC
The Higher Education Ministry has reappointed Professor Dato’ Dr. Daing Nasir Ibrahim as Universiti Malaysia Pahang (UMP)’s Vice-Chancellor for another two years, effective from May 16, 2013.